KAJIAN YURIDIS PENGALIHAN HAK PAKAI PUBLIK (SUDI DI BELANG BENANGKA KABUPATEN ACEH TENGAH) - Weirasi Enginte; Muhammad Yamin; Zaidar Zaidar (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
Land has a very important role for human life because land is a place to carry out life activities, because of its large role it can also cause legal problems, such as the existence of Land Use Rights Number 1 on behalf of the Regional Government of Nanggroe Aceh Darussalam Province which was granted in 1989 by The Ministry of Basic Chemical Industry based on the Grant Charter No. 566/DJ.KD/VIII/1983 dated August 3, 1983. It is located in Simpang Kelaping village, Kala Pegasing, Kung, Pegasing District, Central Aceh Regency, better known as Belang Bebangka, with an area of ​​122 Ha. The land is partly from State land and partly from customary-owned land, initially the land will be built by the Takengon Paper Project by the central government in this case the Ministry of Basic Industry/Mining. 1 since it was handed over by the Ministry of Basic Industry in 1989 until now, what has happened is that people who claim to be Penghulu Gading, namely groups of heirs and those who claim to have rights to the land on the land, manage directly, and even some have transferred their rights by selling buy. The problems that have occurred in this area have been going on for years until now there has not been a meeting point between the Aceh Provincial Government, Central Aceh District Government and the community. In this regard, the guarantee of legal capacity is very necessary.